Sequential Quadratic Programming Method of Cabin Optimization - Li, Ming Ming; Song, Fang Zhen; Liu, Han; Song, Bo (Applied Mechanics and Materials, 2014)
The basic principle of sequential quadratic programming method and the concrete implementation steps in MATLAB are expounded. Sequential quadratic programming method is used for the cabin structure optimization. In the optimization, the minimal sizes of components stipulated by the rules are used as size constraints, the frequencies required by the rules are used as performance constraints and the minimum lightness of the ship are used as objective. Finite element analysis of the ship structure optimized is done and the results obtained show that both the maximum equivalent stress and the maximum shear stress meet the requirements and first three order frequencies of the cabin structure are also far away from the working frequency of propeller and host. The optimization reduces the weight of the cabin under the condition of meet the static characteristic and dynamic characteristic.